Inventarios de bienes municipales (2017) - Salamanca (Provincia). Diputación Provincial; Archivo de la Diputación de Salamanca
- Boada. - Las Casas del Conde - Castellanos de Villiquera - Cerezal de Peñahorcada - El Manzano, Fuenteguinaldo - La Peña - Villamayor - Villoruela - Vilvestre